Al-Kharoubi's Efforts in Interpretation (Journal of Human Sciences, 2020)
This study aims at shedding light on the efforts of Imam Muhammad bin Ali Al-Kharoubi, one of the leading figures in Libya in the field of interpretation. It also focuses on his concern for the interpretation of the Noble Qur’an by his contemporaries, the impact of the methods of previous interpretations on his own interpretation and his approach which linked Sharia and Truth through his descriptive and analytical methods. One of the most important results of this study is that Imam al-Kharoubi was born in 890 AH/1485 CE in Libya, but not as it was stated in some sources that he was born in Sfax. He grew up in a righteous family, in the lap of Sufism, in the hands of his parents and his mentor Ahmad Zarrouk. He was considered as one of the Maliki scholars, the top advocates of Maliki school of thought in the Arab Maghreb. In his interpretation, he combined the outward and the inward sciences to unite the Sharia with the truth. Besides his interpretation, he had many publications such as Riyadh Alazhar and Kanz Alasrar including Explanation of Mankind in the Faults of the Soul, Unambiguous Manners and Secrets of.